Experimental investigation and thermodynamic modeling of the U–Nb system. (10th August 2021) - Mo, Chuan; Mo, Wenlin; Zhou, Peng; Bian, BaiXue; Du, Yong; Fa, Tao; Zhang, Pengguo; Li, Ruiwen; Zhang, Yanzhi; Zhang, Changsheng; Xia, Yuanhua; Wang, Xiaolin
Abstract: The phase equilibria and thermodynamic properties of the U–Nb system were investigated through experiments and thermodynamic modeling. In the experiments, a series of samples with different content of Nb were prepared by arc melting. The Nb content covers the entire composition range of the U–Nb binary system. After solidification, the samples were annealed and then analyzed by X-ray diffraction, scanning electron microscopy, energy dispersive X-ray spectroscopy, differential scanning calorimeter and neutron diffraction. The equilibrium phases, including γ1 (U-rich bcc), αU, and γ2 (U-depleted bcc), were determined in detail from the experimental characterization. The occurrence of the invariant reaction γ1 → αU + γ2 was confirmed, and the reaction temperature and composition were accurately identified. Moreover, the experimental findings clarify the dispute between the Dwight and Terekhov theories regarding the phase region (i.e., whether the phase region is αU + γ1 or βU + γ2 ). Furthermore, the U–Nb phase diagram was reassessed by incorporating the present experimental data and previously published reliable experimental data from the literature. A set of self-consistent thermodynamic parameters were developed using CALPHAD (Calculation of phase diagrams), and the calculations reasonably agree with the experimental observations.